Równość wyborów na przykładzie Polski oraz niektórych krajów Ameryki Południowej - Brzeziński, Mateusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The principle of equal voting, recognized in European countries as one of the foundations of the functioning of the democratic state of law, seems to be differently perceived in some South American countries. This article compares the current system in Poland with some clear examples from South American countries. This comparison aims to highlight some of the fundamental differences in perceptions not only of the voting rights of ethnic minorities, but also of the electoral rights of individuals in general (in particular – gender equality). It is also justified to show some paradoxes in the understanding of this principle, for example in ethnicity guaranteed places (example of Bolivia – when people identify with any ethnic group are the majority of the population) or undermine the material equality of voting (Ecuador example).
Keywords: elections; privilege; South America; minority; ethnic group; equality